The effect on heart rate variability of acclimatization to a humid, hot environment after a transition across five time zones in elite junior rowers - Dranitsin, O. V. (European Journal of Sport Science, 2008)
The aim of this study was to examine the simultaneous effect on heart rate variability (HRV) of acclimatization to a hot, humid environment and a transition of five time zones in elite junior rowers. Thirteen rowers (12 males and 1 female) participated in the study. Each rower was monitored during training camps in temperate and in humid, hot conditions before and during the Junior Rowing World Championship. All participants recorded the lengths of high-intensity training sessions, and R-R (the time between the R peaks of consecutive QRS complexes) intervals were measured every morning after awakening. Compared with baseline values taken during training before the transition to the new time zone and climate, HRV indices during first 3 days of acclimatization remained unchanged. On the fourth and fifth days of acclimatization, significant decreases in measures of heart rate variability in the standing position were observed. Beginning from the sixth day of acclimatization and for all subsequent days, the HRV indices, while standing, returned to baseline values and were not significantly different from baseline. Despite this, there were no significant changes in HRV measures in a supine position until the eighth day of acclimatization. R-R intervals decreased and mean heart rate increased significantly (P<0.001) during days 8-10 of acclimatization. In conclusion, major physiological adaptation of HRV indices in the standing position during acclimatization to a humid, hot environment, with a transition across five time zones, occurs within the first 5 days in elite athletes before returning to baseline. Indices of heart rate variability in the supine position correlate with the length of high-intensity training sessions on the previous day.